Literary citizenship and the politics of language: the Galician literary field between 1939 and 1965 - García-Liñeira, M (2015)
My thesis, Literary Citizenship and the Politics of Language: The Galician Literary Field between 1939 and 1965, is the first attempt to examine the building process of Galician national literature by focusing on one of its constitutive elements, the linguistic criterion. Drawing on Mario Santana's concept of literary citizenship, which can be defined as membership of a literary community, it pays attention to the development of the idea that Galician literary citizenship is language specific, in other words, that to be a member of the national literature, writers have to write in Galician. It does so by focusing on one of the most neglected periods in Galician and Spanish Studies (1939–1965). Chapter one, 'Going Public: The Adventure of Galician Publishing, 1939–1965', presents the first ever account of the publishing world in the studied period. Chapter two, 'From Region to Nation: Galician Literary Studies', argues that the main battleground in the definition of Galician literary citizenship was the field of Galician literary studies, where the concept of literary citizenship was naturalised and then institutionalised. Chapter three, 'Negotiating Identities', explores writers' language choices, paying special attention to those who wished to earn a language-specific Galician literary citizenship. Apart from native and exophonic writers, the chapter addresses writers who did so through translation. Chapter four, 'No Man's Land: Female Writing and Language', argues that female writers had a double-edged experience in the literary field. The patriarchal literary institutions were interested in their symbolic capital but they exercised firm control over them. The conclusion, 'A New raison d'être for Galician Literary Studies', summarises the main argument put forward by this thesis, that to understand fully the development of Galician literary citizenship, literature must be studied outside the national framework.